351 Nephrology research – coping in young people with chronic kidney disease (CKD). (17th August 2022) - Muhammad, Shahid
Abstract : Aims: Chronic kidney disease (CKD) is an irreversible disease with physiological, psychological and psychosocial challenges, especially for young people. Objectives: The objective of this phenomenological study was to identify coping strategies in two groups of young people aged 12–18 years. In one group, the young people were healthy and in the other group, the young people had stage 4–5 CKD. Methods: Young people with CKD (stages 4–5) (n ¼ 7) (mean age ¼ 11.5 yrs.) and young healthy people (n ¼ 7) (mean age ¼ 14 yrs.) were recruited from a Children's Hospital and Youth Club respectively, and were invited to take part in one face-to-face, semi-structured interview. Results: Data analysis showed 11 different coping themes. Conclusion: It can be concluded from the interviews that young healthy people and those with CKD alike, utilise a range of coping strategies. The themes derived can prompt researchers to potentially develop a coping measure for a young CKD population. However, a longitudinal study would help to recognise coping strategies young people adopt over time and provide a pathway for the development of a formal coping framework.